2020
DOI: 10.1155/2020/9758289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12-Week Exercise Program on Enzyme Activity of Serum Matrix Metalloproteinase-9 and Tissue Inhibitor of Metalloproteinase-1 in Female Patients with Postmenopausal Osteoporosis: A Randomized Control Study

Abstract: Background. Osteoporosis is a disease characterized by decreased bone density and destruction of bone microarchitecture. Indicators for altered bone homeostasis are changes in the serum level of matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs). The purpose of the current study was to evaluate the effect of a 12-week exercise program on enzyme activity of serum MMP-9 and TIMP-1 in postmenopausal osteoporotic patients. Materials and methods. Participants were randomized in two groups: exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…None of the studies included in the current review reported that they defined osteoporosis, post‐menopausal woman (a group more susceptible to osteoporosis), and RA as exclusion factors. Additionally, other studies have shown that physical exercise, which is known to stimulate bone resorption, leads to an increase in serum TIMP‐1 level (and increase in MMP‐8 and MMP‐9) suggesting that degree of exercise might be another potential confounder for TIMP‐1 concentration in oral fluids 29,33 . All these studies measured TIMP‐1 levels in serum and not in saliva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the studies included in the current review reported that they defined osteoporosis, post‐menopausal woman (a group more susceptible to osteoporosis), and RA as exclusion factors. Additionally, other studies have shown that physical exercise, which is known to stimulate bone resorption, leads to an increase in serum TIMP‐1 level (and increase in MMP‐8 and MMP‐9) suggesting that degree of exercise might be another potential confounder for TIMP‐1 concentration in oral fluids 29,33 . All these studies measured TIMP‐1 levels in serum and not in saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies have shown that physical exercise, which is known to stimulate bone resorption, leads to an increase in serum TIMP‐1 level (and increase in MMP‐8 and MMP‐9) suggesting that degree of exercise might be another potential confounder for TIMP‐1 concentration in oral fluids. 29 , 33 All these studies measured TIMP‐1 levels in serum and not in saliva. However, during periodontal inflammation serum proteins leak into the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 [277], S100A12 [278], IGF2 [279], GPR84 [280], SOCS3 [281], ANXA3 [282], IGFBP2 [283], NOS1AP [284], G0S2 [285], HP (haptoglobin) [286], MMP8 [287], SLC6A19 [288], OSM (oncostatin M) [289], S100A8 [290], FFAR3 [291], ARG1 [292], ADM (adrenomedullin) [293], S100A9 [294], NRG1 [295], IL1R1 [296], IL4R [297], TSPO (translocator protein) [298], TXN (thioredoxin) [299], PLAU (plasminogen activator, urokinase) [300], SLC11A1 [301], TRPM2 [302], RETN (resistin) [303], NLRC4 [304], CD55 [305], ALOX5AP [306], GPR160 [307], TRPM6 [308], ALOX5 [309], IL1RN [310], ADM2 [311], DGAT2 [312], TLR4 [313], ENTPD1 [314], GRB10 [315], IL17RA [316], IRS2 [317], MGAM (maltase-glucoamylase) [318], FADS2 [319], SLC22A4 [320], KCNJ15 [321], PPP1R3B [322], CTSD (cathepsin D) [323], SERPINB11 [324], COL4A3 [325], ADAM12 [326], SOX5 [327], CD80 [328], ERBB2 [329], POU2AF1 [330], FASLG (Fas ligand) [331], SOX13 [332], BANK1 [333], IL2RA [334], AQP3 [335], CCR4 [336], CD74 [337], FCRL3 [338], ITGB7 [339], PARP1 [340], TXNIP (thioredoxin interacting protein) [341], SUV39H1 [342], HSPA8 [343], ETS1 [344], ELP5 [345] and PDCD4 [346] might be important for diabetes mellitus progression. Previous research found that MMP9 [347], CBS (cystathionine beta-synthase) [348], IGF2 [349], IGFBP2 [350…”
Section: Discussionmentioning
confidence: 99%
“…Considering the chronic effects of exercise on enzyme activities, Filipović, Gopčević [26] investigated the effects of a 12-week exercise program on serum MMP9 and TIMP1 activity in postmenopausal patients with osteoporosis. This exercise program included aerobic, resistance and balance exercises.…”
Section: Discussionmentioning
confidence: 99%